Psychological outcomes and changes in health-related quality of life in young and middle-aged patients with first-onset stroke after rehabilitation training - Han, Chao; Yu, Dahai; Sun, Xueli; Liang, Ziyan (Frontiers in Psychiatry, 2026)
ObjectivesThe primary objective of this study is to determine the changes in psychological well-being and health-related quality of life (HRQOL) among young and middle-aged individuals who have experienced their first stroke and undergone structured rehabilitation training.MethodsThis prospective analysis included 203 young and middle-aged individuals who had experienced their first stroke and took part in a comprehensive rehabilitation program conducted in China. Patients were classified into “Unremarkable” or “Impaired” groups based on their pre-rehabilitation scores in each scale of the SF-36, SCL-90, and BDI-II scales using established cut-off values from prior research. The rehabilitation program consisted of physical therapy, occupational therapy, and psychological counseling. The rehabilitation program began at least 4 weeks after stroke onset and was carried out over a period of 6 to 8 weeks, with participants attending five sessions per week. Neuropsychological assessments, including the SF-36, SCL-90, and BDI-II scales, were conducted before and after rehabilitation to measure changes in HRQOL, psychological outcomes, and depressive symptoms.ResultsIn terms of HRQOL, notable improvements were observed, particularly in the “impaired” group. Following rehabilitation, key indicators, including physical function, overall health, bodily pain, and vitality, showed considerable enhancement (P < 0.001). Regarding psychological outcomes, the “impaired” group demonstrated substantial reductions in symptoms such as aggression, anxiety, obsessive-compulsive behaviors, and paranoid ideation (P < 0.001). Furthermore, assessments using the BDI-II and SCL-90 depression scales indicated a significant decrease in depressive symptoms within the “impaired” group (P < 0.001), whereas no meaningful changes were noted in the “no significant abnormalities” group. These results demonstrate the effectiveness of rehabilitation in improving both psychological well-being and HRQOL in patients with more severe pre-rehabilitation impairments.ConclusionRehabilitation training significantly improves psychological outcomes and HRQOL in young and middle-aged individuals with first-onset stroke, particularly those with more severe baseline impairments. These findings support the integration of multidisciplinary rehabilitation programs in the management of stroke recovery, with significant benefits for both physical and psychological recovery.